The Efficiency of Pre-Sowing Seed Treatment with Trace Element Solutions - Smirnova , Tatiana; Temereva, Irina; Panov, Sergei; Stepanova, Tatiana (KnE Life Sciences, 2021)
This article analyzes the results of four-year research which examined the effectiveness of pre-sowing treatment (soaking, spraying) of white cabbage seeds with trace element solutions of various concentrations. The research was conducted under laboratory conditions at the Agricultural Chemistry and Soil Science Department of Omsk State Agrarian University with a mid-season-ripening, medium-yielding and high-yielding variety of white cabbage (Sibiryachka 60) found in the Omsk region. 0.02%, 0.04% and 0.05% solutions of ZnSO4 ⋅ 7H2O and 0.01%, 0.02%, 0.03% and 0.05% solutions of H3BO3 were used in the experiment. The cabbage seeds were soaked in water (control) and in trace element solutions for 6-12-24 hours. The germination energy and germination capacity of the seeds, the zinc distribution, and the biometric indicators of the seedlings and of the cabbage transplant seedlings were determined. The optimal concentrations of the trace element solutions and the optimal duration of pre-sowing treatment were established, which stimulated the development of seedlings and increased seed germination by 5-9%. It was noted that, compared with the control, 2 times more plants reached the 6-leaf phase by the time of planting when transplant seedlings were treated with a boric acid solution in the optimal concentration, and 3.6 times more plants did when fertilized with zinc. Based on the results the following is recommended for implementation in production: soaking seeds in a 0.03% solution of Н3ВО3; soaking seeds in a 0.04% solution of ZnSO4; soaking time - 6 hours; a 1:2 ratio of seeds to the solution; and concentration of solutions per element for boron – 0.005% and zinc – 0.01%. Keywords: white cabbage, seeds, micro-fertilizers, pre-sowing treatment